Didymocarpus moellerii (Gesneriaceae): a new species from northeastern India - Joe, Alfred; Hareesh, Vadakkoot Sankaran; Prashob, Pulpara; Sabu, Mamiyil (Phytotaxa, 2016)
Didymocarpus moellerii, a new species from northeastern India is described and illustrated with photographs. Information on its ecology is provided as well. The new species is morphologically similar to D. glandulosus and D. tonghaiensis but can be easily distinguished by a combination of characters such as glabrous peduncle, orbicular purple bracts, puberulent anthers, orange-red corolla with white stripes at the throat, longer ovary, bulged ovary apex and cup-like disc.